As if living like others: An idealisation of life in group homes for people with intellectual disability. Issue 4 (1st October 2020) - Björne, Petra
ABSTRACT: Background: People with Intellectual Disability (ID) in Sweden should be enabled to live like others . This life like others is realised in group homes that have little in common with the typical home. Method: A reading of Appiah's As if is used to discuss how people with ID are supported in Sweden. Current national data are presented within the framework of idealisation, the use of (useful) untruths to navigate a complex context. Results : Small group homes should allow people with ID to communicate their preferences and exert real influence over how support is provided. Instead, times of budget austerity require the efficient use of resources in ever larger settings, where normalisation of deviance is prevalent. Conclusions : Although the stated aim is that people with ID live like others, the idealisation is rather that they live as if they live like others . This is generally not discussed, possibly due to de-differentiation.